2013
DOI: 10.1016/j.jadohealth.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Polysubstance Use in a Nationally Representative Sample of 10th Graders in the United States

Abstract: Purpose The current study examines the prevalence and demographic correlates of self-reported substance use and identifies subgroups of polysubstance users among a cohort of US 10th grade students. Methods A nationally representative school-based cohort of US 10th grade students completed the NEXT Generation Health Study baseline survey in the spring of 2010 (N = 2,524). Results Past-year use of marijuana was most common among illicit drugs (26%), followed by misuse of medication (9%) and use of other illi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
141
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 33 publications
(49 reference statements)
7
141
2
2
Order By: Relevance
“…Psychoactive substance use (PASU) among adolescents is an increasing subject of social and public health concern in most parts of the world (Conway et al, 2013;Thompson, Rivara, & Whitehill, 2015;Yusoff et al, 2014). Previous and recent decades have seen both scientific sources and popular press in developed and developing countries devoting priority to PASU among youth (Botvin & Griffin, 2007;Cronk & Sarvela, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychoactive substance use (PASU) among adolescents is an increasing subject of social and public health concern in most parts of the world (Conway et al, 2013;Thompson, Rivara, & Whitehill, 2015;Yusoff et al, 2014). Previous and recent decades have seen both scientific sources and popular press in developed and developing countries devoting priority to PASU among youth (Botvin & Griffin, 2007;Cronk & Sarvela, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The home initially and traditionally is considered the primary source where school-age children begin to draw their views of alcohol and its subsequent use (Conway et al, 2013;Wallace & Muroff, 2002;Yusoff et al, 2014). Furthermore, it has been suggested that family attitudes towards PASU behavior, poor and inconsistent family management practices, high levels of family conflict, and low family bonding work in unison to enable substance use among adolescents (Wallace & Muroff, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Primary-sampling units consisted of school districts or groups of school districts stratifi ed across the nine U.S. census divisions. Within this sampling framework, 80 schools out of 137 (58.4%) randomly selected schools agreed to participate starting in the 2009-2010 school year (Conway et al, 2013). Within each participating school, 10th-grade classes were randomly selected to participate; student assent and parental consent were obtained.…”
mentioning
confidence: 99%
“…[19][20][21] Mood disorders have also been found to be significantly associated with SUDs, including alcohol, marijuana, tobacco, and polysubstance use. 22,23 Despite the high prevalence of BHCs among adolescents, many go unidentified and untreated. The Affordable Care Act and federal and state mental health and addiction treatment parity laws all contain provisions aimed at increasing access to treatment for BHCs.…”
mentioning
confidence: 99%